Implementasi Metode Wahdah Dalam Meningkatkan Hafalan Al-Qur’an Di Pondok Pesantren An-Nur Surodadi Gringsing Batang 2024/2025 - M. Fawwaz Sauqi F; Ngarifin Shidiq; Ahmad Robihan (STIKES Columbia Asia Medan, 2025)
This study aims to describe the strategy of memorizing the Qur'an through the Wahdah method in improving memorization of the Qur'an at the An-Nur Surodadi Gringsing Islamic Boarding School. The approach used is a qualitative field with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of the Wahdah method in improving memorization of the Qur'an at the An-Nur Islamic Boarding School is driven by internal factors such as the enthusiasm of the students to use their time as best as possible to memorize the Qur'an, tutors who always provide motivation and also the right memorization method, a conducive memorization place, and adequate facilities. However, challenges such as the ability of the students to memorize the Qur'an varies, students who are sick so they cannot increase their memorization, students who lack awareness of the importance of memorizing the Qur'an still need to be considered. Guidance and direction by the tutors have proven effective, so that the students are able to memorize the Qur'an well and fluently. This is supported by the use of the right memorization method